Notes on floral visitors in Seemannia sylvatica (Kunth) Hanstein (Gesneriaceae) - Cairampoma, Lianka (2012)
Pollination in Gesneriaceae commonly is associated with syndromes of ornithophily or melittophily, and usually others visitors are robbers of nectar. We present a note about the fauna that visit the flowers of Seemannia sylvatica in Cusco, where hummingbirds and insects were recorded visiting the flowers. Based on floral characteristics and behavior of floral visitors, we suggest that the flowers of S. sylvatica present an ornithophily syndrome. Therefore, only hummingbirds are pollinators, while the insects are not involved in pollination and only steal nectar from flowers.